Uji Organoleptik Dan Kadar Protein Es Krim Dengan Penambahan Kacang Tolo (Vigna Unguiculata) Dan Larutan Ubi Jalar Ungu Sebagai Pewarna Alami - Prihatin, Anik (2016)
Tolo beans is one of the kinds of nuts high relatively high protein content of 22,9 g, fat 1,4 g and carbohydrates 61,6 g. Purple potato as natural colour has anthocyanin pigments. The purpose of this research was to determine content of organoleptic andprotein dissolved. The method used was a research experiment with Completely Randomized Design (CRD) two factors, factor I beans tolo (50 g, 45 g dan 40 g) and factor II purple potato extract (35 ml, 30 ml dan 25 ml) with 2 replications. Data were analyzed with descriptive of qualitative and quantitative. The result showed that U1K1 (tolo beans 50 g : purple potato extract 35 ml) is the highest contens of protein 0,77 %, and highest melted speed of 58 minutes 50 seconds. The best quality ice cream is a old purple color, sweet taste, milk taste, very soft the texture and society acceptence. It was concluded that the tolo beans with purple potato solution no effect on the contents of proteins dissolved. The result statistic analisis with spss versi 15.0 showed that Asymp.sig 0,90 > 0,05, Ho acceptence, no effect on the contents of organoleptic and protein ice cream.